Pengaruh brand signature dan brand familiarity terhadap brand attitude - Mustikasari, Meilan; Rusfianti, Sarah; Yuliana, Lingga (Jurnal Ilmu Manajemen, 2023)
This study examines how brand familiarity and signature affect brand attitude. The urgency in this study was discovering a research gap with the presence of brand familiarity variables as independent and dependent variables. Research on brand signature and brand familiarity on brand attitude has never been done before, so this becomes a novelty. This novelty is a modification of the research that has been raised. The quantitative descriptive approach is used in this study. Using purposive sampling as a sample method. Primary and secondary data are the sources used. 107 Scarlett brand customers participated in the study as respondents. The analysis tool used in this test is Partial Least Square (PLS). According to research, all hypotheses are significant. The managerial implication in this study is that the brand signature for the Scarlett brand is considered essential. This result relates to logos, designs, and colours so that they can become points of difference from other brands. In developing a brand attitude, consumers must also understand aspects of the brand signature to experience clarity in having a brand in a store or retail. There are many existing brands, so at least consumers can easily choose a brand. Scarlett must strive so that consumers who are the target market will always choose local brands.